2018
DOI: 10.1002/soej.12258
|View full text |Cite
|
Sign up to set email alerts
|

Economic Freedom and Exercise: Evidence from State Outcomes

Abstract: Exercise is an important part of a healthy lifestyle and influences a variety of health outcomes. Regions vary in their levels of exercise due to geography, climate, culture, and policy. The extent to which a country's policies are consistent with economic freedom has been found to be positively associated with greater participation in physical activity. We empirically investigate the relationship between economic freedom and exercise across U.S. states. Contrary to the cross‐country results, we find that stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…We start with an assumption that there are at least two institutional regimes, under which inequality can either be detrimental to performance of athletes (regime of low level of economic freedom), or irrelevant for the performance of athletes (regime of high level of economic freedom). Under the regime of low economic freedom, athletes cannot easily appropriate the gains from winning a medal and thus there are fewer incentives 2 However, we should point out that Hall et al (2018) found a negative association between economic freedom and physical exercise in American states whereas Ruseski and Maresova (2014) found a positive association when focusing on countries instead.…”
Section: Methods and Datamentioning
confidence: 91%
See 1 more Smart Citation
“…We start with an assumption that there are at least two institutional regimes, under which inequality can either be detrimental to performance of athletes (regime of low level of economic freedom), or irrelevant for the performance of athletes (regime of high level of economic freedom). Under the regime of low economic freedom, athletes cannot easily appropriate the gains from winning a medal and thus there are fewer incentives 2 However, we should point out that Hall et al (2018) found a negative association between economic freedom and physical exercise in American states whereas Ruseski and Maresova (2014) found a positive association when focusing on countries instead.…”
Section: Methods and Datamentioning
confidence: 91%
“… 2 However, we should point out that Hall et al . (2018) found a negative association between economic freedom and physical exercise in American states whereas Ruseski and Maresova (2014) found a positive association when focusing on countries instead.…”
mentioning
confidence: 99%
“…In addition, the literature highlights the existence of a negative relationship between economic freedom and some specific health outcomes in developed countries: for instance, Lawson et al (2016) show that as economic freedom increases in advanced economies, so does the body mass index of men, meaning that liberalism seems to ease obesity. Consistently, Hall et al (2018b) show that, in the U.S.A., people living in economically freer states practice physical exercise less, which may lead to worse health conditions. However, also in this case, the evidence provided by the literature is mixed: Ruseski and Maresova (2014) find the opposite result, studying the relationship existing between economic freedom and sports activities in a sample of countries.…”
Section: Related Literaturementioning
confidence: 90%
“…While the literature generally praises economic freedom for its positive effects, negative ones are also found in the literature. For example, higher levels of economic freedom are associated with lower rates of participation in exercise in the US (Hall et al, 2018) and higher obesity rates (Ljungvall, 2013;Lawson et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%